In vitro Models of the Small Intestine for Studying Intestinal Diseases - Jung, Sang-Myung; Kim, Seonghun (Frontiers in Microbiology, 2022)
The small intestine is a digestive organ that has a complex and dynamic ecosystem, which is vulnerable to the risk of pathogen infections and disorders or imbalances. Many studies have focused attention on intestinal mechanisms, such as host–microbiome interactions and pathways, which are associated with its healthy and diseased conditions. This review highlights the intestine models currently used for simulating such normal and diseased states. We introduce the typical models used to simulate the intestine along with its cell composition, structure, cellular functions and external environment and review the current state of the art for in vitro cell-based models of the small intestine system to replace animal models, including ex vivo, 2D culture, organoid, lab-on-a-chip and 3D culture models. These models are described in terms of their structure, composition and co-culture availability with microbiomes. Furthermore, we discuss the potential application for the aforementioned techniques to these in vitro models. The review concludes with a summary of intestine models from the viewpoint of current techniques as well as their main features, highlighting potential future developments and applications.